Tetrasubstituted Furans by Nucleophile-Induced Cleavage of Carbonyl Ylide–DMAD Cycloadducts - Dobesch, Matthias; Greiner, Julian; Maas, Gerhard (Synthesis, 2020)
Compounds incorporating a 4-aza-8-oxabicyclo[3.2.1]oct-6-en-2-one moiety, which were prepared by a tandem carbenoid carbonyl ylide cyclization/[3+2]-cycloaddition reaction from ethyl 2-diazo-3-oxo-4-phthalimidobutanoates, undergo a nucleophile-induced two-bond ring cleavage when treated with protic heteronucleophiles. In this manner, tetrasubstituted furantricarboxylates, tethered with α-amino acids, esters, thioesters, and amides by a 2-carbonylphenyl moiety, are obtained.
Keywords: diazo compounds; carbonyl ylides; carboxamides; cycloaddition; furan